Self-care Education on the Utilisation of Toga for Diabetes Mellitus Treatment in Gampong Serambi Indah, West Langsa District, Langsa City: Edukasi Asuhan Mandiri Pemanfaatan Toga Untuk Pengobatan Diabetes Melitus Di Gampong Serambi Indah Kecamatan Langsa Barat Kota Langsa - Maria Irwani; Zakirullah; Nora Hayani; Amelia Sari; Defri Aroni (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2025)
Indonesia is ranked seventh out of ten countries with the largest number of diabetes patients, so Indonesia is on diabetes alert status. With a diabetes prevalence of 6.2 percent, more than 10.8 million people in Indonesia in 2020, suffer from diabetes. On the other hand, promotive-preventive initiative actions are efforts to empower individuals to be able to take care of themselves, maintain health, and overcome minor health problems independently. Through the use of family medicine gardens (TOGA) and skills, individuals in families, groups, or communities have practiced traditional self-health care. This community service activity aims to increase awareness and skills in the field of self-care values ​​​​by using TOGA to manage diabetes mellitus. The participatory community empowerment model is the approach used to expand this knowledge. Activities are carried out in Gampong Serambi Indah, Langsa Baro District, West Langsa Regency, and Langsa City. For three months in 2024, instructors from the D-III Langsa Nursing Department carried out this activity. The target population was given knowledge about plants that are efficacious in treating diabetes mellitus and the correct processing methods for use as self-care for the treatment of diabetes mellitus.